Acute Liver Failure - Rajaram, Priyanka; Subramanian, Ram (Seminars in Respiratory and Critical Care Medicine, 2018)
Acute liver failure (ALF) is a condition that can rapidly progress to multiorgan failure. This article focuses on the diagnosis and management of ALF. We provide a detailed review of the common etiologies of ALF, including acetaminophen overdose, viral hepatitis, drug-induced liver injury, Wilson's disease, and autoimmune hepatitis. The article then addresses how to recognize ALF and reviews the role of common laboratory and imaging tests in establishing this diagnosis. The remainder of the article details the management of hepatic and extrahepatic organ dysfunctions in ALF. The article concludes with a discussion regarding the prognostication of patients with ALF and the criteria for considering liver transplantation.
Keywords: acute liver failure; hepatic encephalopathy; acute renal failure; intracranial hypertension; acetaminophen toxicity